1980
DOI: 10.1056/nejm198005293022201
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Antigen-Specific Suppressor Cells during Allergy Desensitization

Abstract: We used a suppressor-cell assay to study a possible mechanism of allergy desensitization. Before specific immunotherapy, blood mononuclear cells from 20 patients with ragweed hayfever failed to exhibit suppressor activity in vitro after stimulation by ragweed antigen E. However, when the 10 patients with allergic rhinitis had been desensitized by injections of ragweed extract, their mononuclear cells specifically suppressed a ragweed proliferative response six and 12 months after desensitization was begun (31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
0
3

Year Published

1986
1986
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(90 citation statements)
references
References 29 publications
4
83
0
3
Order By: Relevance
“…It has been reported that SIT induces a subpopulation of T cells that can suppress specific antigen-induced T-cell proliferation (45,46). Thus, immunotherapy could act by shifting the balance from T helper toward T suppressor cells, switching off the production of specific IgE.…”
Section: Effect On T Cellsmentioning
confidence: 99%
“…It has been reported that SIT induces a subpopulation of T cells that can suppress specific antigen-induced T-cell proliferation (45,46). Thus, immunotherapy could act by shifting the balance from T helper toward T suppressor cells, switching off the production of specific IgE.…”
Section: Effect On T Cellsmentioning
confidence: 99%
“…Although complications derived from the impurity of allergens have been overcome by the production of purified recombinant allergens, provocation of possibly life-threatening anaphylaxic reactions remains to be a serious adverse effect. In contrast, immunological mechanisms for the hyposensitization per se have been an issue of much arguments for decades, and a number of mechanisms have been proposed, including generation of blocking Ab, suppressor cells, induction of specific anergy, and clonal deletion (2,3,6,7). Recently, shift of the balance between Th1 and Th2 cell responses has been stressed as the major underlying cause for atopic diseases, in which the Th2 response producing IL-4 predominates over Th1 response producing IFN-␄ resulting in the production of excess IgE Ab (8 -10).…”
mentioning
confidence: 99%
“…It has been suggested that selective stimulation of Ts cells or a new formation of antigen-specific Ts cells (20)(21)(22) may be responsible for suppressing IgE synthesis during immunotherapy. In man, isotype-as well as antigen-specific Ts cells have been found in patients treated with immunotherapy, but not in untreated controls (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%